1984
DOI: 10.1017/s0068245400019845
|View full text |Cite
|
Sign up to set email alerts
|

Lead Figurines from the Menelaion and Seriation

Abstract: The lead figurines from recent excavations at the shrine of Helen and Menelaus are discussed, excluding those in the form of wreaths, which were well over half the total of almost 6,000. Five hundred and sixty-one moulds are distinguished, divided between sixty-one varieties. A chronology is attempted on the basis of three methods, stratigraphy, seriation, and typology and a tentative sequence is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 1 publication
3
14
0
1
Order By: Relevance
“…The Traquair Collection also allows us to test, through the close analysis of a small sample, the applicability and chronological utility of the long-standing Laconian lead figurine typology in dating and describing figurines for which no or only very approximate contextual data are available. In this regard, our study supports and supplements the issues raised by Cavanagh and Laxton (1984) in their study of figurines from the more recent Menelaion excavations, where they repeatedly found it necessary to rely on stratigraphic and contextual data rather than typology when seeking to assign precise dates to lead figurines and associated levels. The Traquair Collection complements Cavanagh and Laxton's analysis by approaching the issue of typology from the standpoint of a decontextualised museum collection.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…The Traquair Collection also allows us to test, through the close analysis of a small sample, the applicability and chronological utility of the long-standing Laconian lead figurine typology in dating and describing figurines for which no or only very approximate contextual data are available. In this regard, our study supports and supplements the issues raised by Cavanagh and Laxton (1984) in their study of figurines from the more recent Menelaion excavations, where they repeatedly found it necessary to rely on stratigraphic and contextual data rather than typology when seeking to assign precise dates to lead figurines and associated levels. The Traquair Collection complements Cavanagh and Laxton's analysis by approaching the issue of typology from the standpoint of a decontextualised museum collection.…”
Section: Introductionsupporting
confidence: 83%
“…An assemblage of nearly 6000 additional figurines was recovered in the BSA's renewed excavations at the Menelaion during the 1970s under the direction of H.W. Catling (Catling 1976–7; Cavanagh and Laxton 1984).…”
Section: The Sanctuary Of Artemis Orthia and Laconian Lead Figurinesmentioning
confidence: 99%
See 1 more Smart Citation
“…21. Dawkins 1929Cavanagh & Laxton 1984. Le corpus total des satyres et Silènes 25 laconiens représente donc 6 vases à igures noires, 9 bronzes, 1 igurine de terre cuite, 1 base de perirrhanterion en terre cuite 26 et plusieurs masques votifs en terre cuite (ig.…”
Section: Satyresunclassified
“…These designations are frequently also applied to chronological periods. Hodkinson (1998) has proposed a revised chronology, based on the conclusions of the original excavators (Dawkins 1929), the revision by Boardman (1963), and the findings of Cavanagh and Laxton (1984). Hodkinson's suggestion is that figurines may date from around 650 bc , with a peak in Wace's Lead III–IV (580–500 bc ) of over 68,000 figurines (Hodkinson 1998, 107, table 2).…”
Section: Lead Votivesmentioning
confidence: 99%